Treating and reducing anxiety and pain in the paediatric emergency department—TIME FOR ACTION—the TRAPPED quality improvement collaborative. Issue 5 (5th February 2018) - Trottier, Evelyne D; Ali, Samina; Thull-Freedman, Jennifer; Meckler, Garth; Stang, Antonia; Porter, Robert; Blanchet, Mathieu; Dubrovsky, Alexander Sasha; Kam, April; Jain, Raagini; Principi, Tania; Joubert, Gary; et al.
Abstract: Background/Objectives: In 2013, the TRAPPED-1 survey reported inconsistent availability of pain and distress management strategies across all 15 Canadian paediatric emergency department (PEDs). The objective of the TRAPPED-2 study was to utilize a procedural pain quality improvement collaborative (QIC) and evaluate the number of newly introduced pain and distress-reducing strategies in Canadian PEDs over a 2-year period. Methods: A QIC was created to increase implementation of new strategies, through collaborative information sharing among PEDs. In 2015, 11 of the 15 Canadian PEDs participated in the TRAPPED QIC. At the end of the year, the TRAPPED-2 survey was electronically sent to a representative member at each of the 15 PEDs. The successful introduction of the chosen strategies by the QIC was assessed as well as the addition of new strategies per site. The number of new strategies introduced in the participating and nonparticipating QIC sites were described. Results: All 15 PEDs (100%) completed the TRAPPED-2 survey. Overall, 10/11 of QIC-participating sites implemented the strategy they had initially identified. All 15 Canadian PEDs implemented some new strategies during the study period; participants in the QIC reported a mean of 5.2 (1–11) new strategies compared to 2.5 (1–4) in the nonactively participating sites. Conclusion: While all PEDs introduced new strategies during the study, QIC-participating sites successfully introduced the majority of their previously identified new strategies in a short time period. Sharing deadlines and information between centres may have contributed to this success.